2008
DOI: 10.1007/s00066-008-1769-7
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Molecular Imaging to Evaluate Radiation Fields in the Adjuvant Setting of Breast Cancer

Abstract: Standard radiation portals in postoperative radiation therapy in breast cancer with lymph node involvement do not automatically result in an adequate dose delivery to the region of highest biological activity. With these preliminary results in a small series it was found feasible to correct this without compromising the dose to the CTV or lungs for patients in whom a preoperative FDG-PET shows nodal involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The procedure at the UZ Brussel has been previously reported [17]. The patients fasted for at least 6 h. Prescanning glucose levels were systematically checked.…”
Section: Fdg Pet Image Acquisition and Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure at the UZ Brussel has been previously reported [17]. The patients fasted for at least 6 h. Prescanning glucose levels were systematically checked.…”
Section: Fdg Pet Image Acquisition and Reconstructionmentioning
confidence: 99%
“…The rationale was to use the scan for staging, and to improve target delineation for subsequent postoperative radiation treatment [17]. In the present study, we evaluated the diagnostic utility of the preoperative PET scan with regard to lymph node involvement, and also evaluated its prognostic value with regard to survival.…”
Section: Introductionmentioning
confidence: 99%
“…Increased mortality hazard observed in association with use of postmastectomy radiotherapy among patients with medial tumors and ≥ 4 ALN+ raises the concern that treatment-related toxicities, particularly with large radiotherapy volumes to encompass IMN, may be a contributing factor counterbalancing the beneficial effects of radiotherapy. Until results of modern trials are available, the possibility that routine radiotherapy of the IMN represents an overtreatment should be discussed and should be balanced against a more targeted approach [2,44,45], in which radiotherapy of the IMN would be limited to patients with IMN metastases [56].…”
Section: Groupmentioning
confidence: 99%
“…Currently, several studies investigated the value of [ 18 F]-fluoro-2-deoxy-D-glucose positron emission tomography (FDG-PET) for staging and treatment planning in various malignancies [3,15,16,24,33]. Also in anal cancer, previous investigations showed that with FDG-PET more involved lymph nodes can be detected than with clinical examination or CT [5,22,28,30].…”
Section: Introductionmentioning
confidence: 99%